"It is possible he is a kind of nut": how the tobacco industry quietly promoted Dr William Whitby. (26th November 2003) - Chapman, S
Abstract : Dr William Whitby was a general practitioner in Sydney who, from 1978 until about 1987, self published two books extolling the virtues of smoking and ridiculing anti-smoking claims. Privately the tobacco industry regarded him as "nutty", while nonetheless believing that his views should be promoted. They quietly supported him by distributing his book, offering legal advice, and persuading him to take media training. Many Australians would have been exposed to his views.